2005
DOI: 10.1143/jjap.44.6289
|View full text |Cite
|
Sign up to set email alerts
|

Sputter Depth Profiling of Multiple Short-Period BN δ-Doped Si by Work Function Measurement

Abstract: Sputter depth profiling of multiple short-period BN δ-doped Si on the basis of work function (WF) measurement using the secondary electron (SE) method was investigated. The concentration of boron in the sample was confirmed to be less than the detection limit of the current Auger electron spectroscopy system. The results revealed that BN δ-doped layers can be detected as a periodic change in the WF of the order of ∼0.01 eV. These results confirmed that sputter depth profiling on the basis of WF measurement usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…It was confirmed that the electron-induced surface segregation of Sc at high temperature can be completely avoided by irradiation of primary electrons under these conditions [13]. Work function was measured at room temperature (RT) by the secondary-electron method [15][16][17][18][19]. In the secondary-electron method, work function is measured as a value relative to that of the reference, DU.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…It was confirmed that the electron-induced surface segregation of Sc at high temperature can be completely avoided by irradiation of primary electrons under these conditions [13]. Work function was measured at room temperature (RT) by the secondary-electron method [15][16][17][18][19]. In the secondary-electron method, work function is measured as a value relative to that of the reference, DU.…”
Section: Methodsmentioning
confidence: 84%
“…In the secondary-electron method, work function is measured as a value relative to that of the reference, DU. DU is obtained from the difference in the onset energy of secondary-electron spectra from the sample and reference surfaces, E sample ÀE ref , using DU = (E sample ÀE ref )/C corr , where C corr is the correction factor required for the precise measurement [15][16][17][18][19]. In the present study, a clean W(1 0 0) surface was used as the reference for the work function measurement, and all the value of work function, DU, is shown as a value relative to that of the clean W(1 0 0) surface.…”
Section: Methodsmentioning
confidence: 99%
“…The apparatus is equipped with a coaxial cylindrical mirror analyzer, an ion gun for sputter cleaning, a Sc evaporator, a sample holder with a heater, and a LEED system specially developed for the observation at high temperature as described below. 16 The work function was measured by the secondary electron method, [18][19][20][21][22] where the work function is measured as a value relative to that of the reference, ⌬⌽. The sample can be heated to approximately 1900 K, which is required for the flashing of the W͑100͒ surface, by electron bombardment using a W filament located behind the W͑100͒ disk.…”
Section: Methodsmentioning
confidence: 99%
“…Hereafter, we define the onset and cutoff energies of the spectrum as the minimum and maximum energies of the MDS spectrum. Because there is the difference in the vacuum level between the sample and spectrometer, the sample was negatively biased to detect all of low-energy electrons emitted from the sample surface [14,[27][28][29][30][31]. In such a measurement, the linearity of the energy scale should be confirmed when different sample biases are applied.…”
Section: Dependence Of Mds Spectra On Sample Biasmentioning
confidence: 99%